Association between Temporary Housing Habitation after the 2011 Japan Earthquake and Mite Allergen Sensitization and Asthma Development - Oshikata, Chiyako; Watanabe, Maiko; Ishida, Masatsugu; Kobayashi, Seiichi; Hashimoto, Kazuhiro; Kobayashi, Naoki; Yamazaki, Akiko; Konuma, Rumi; Kaneko, Takeshi; Kamata, Yoichi; Kuriyama, Shinichi; Yanai, Masaru; et al. (International archives of allergy and immunology, 2021)
We previously reported an increased prevalence of asthma in adults who lived in temporary housing after the 2011 Great East Japan Earthquake. The goal of the current study was to investigate changes in asthma prevalence and mite-specific immunoglobulin E (IgE) titers in temporary housing residents during 2014-2019. By using the Global Initiative for Asthma guidelines, we diagnosed asthma in Ishinomaki city temporary housing residents aged 15 years or older. We then analyzed serum antigen-specific IgE levels to Dermatophagoides farinae (Der f), Dermatophagoides pteronyssinus (Der p), and Aspergillus fumigatus. The prevalence of asthma exceeded 20% across all age-groups throughout the study period. The proportion of study participants with a "positive" antigen-specific IgE titer (i.e., ≥0.35 IUA/mL) was higher in asthmatics than in nonasthmatics for Der f and Der p but not for Aspergillus fumigatus. Among residents ≥50 years old who were diagnosed with asthma, the percentage with a Der f-specific IgE titer ≥0.10 IUA/mL was higher than the proportion with ≥0.35 IUA/mL. Among study participants, asthma onset occurred before the earthquake, during residence in shelters or temporary housing, and (starting in 2016) after moving out of temporary housing. The Der p-specific IgE level was positively correlated with the duration of temporary housing (p < 0.05, r = 0.41) and inversely correlated with the time elapsed since moving out of temporary housing (p < 0.05, r = -0.35). Mite allergen sensitization was found in both asthmatic and nonasthmatic temporary housing residents after the 2011 Japan earthquake and tsunami; asthma developed even after subjects moved out of temporary housing.